2007
DOI: 10.1007/s11060-007-9385-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing potential of the selective cyclooygenase-2 (COX-2) inhibitor meloxicam on human glioma cells

Abstract: The COX-2 protein is frequently overexpressed in human malignant gliomas. This expression has been associated with their aggressive growth characteristics and poor prognosis for patients. Targeting the COX-2 pathway might improve glioma therapy. In this study, the effects of the selective COX-2 inhibitor meloxicam alone and in combination with irradiation were investigated on human glioma cells in vitro. A panel of three glioma cell lines (D384, U87 and U251) was used in the experiments from which U87 cells ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
0
33
1
Order By: Relevance
“…In this study, meloxicam was not observed to have a radiosensitizing effect. it is unclear whether the discrepancy between the results of the study by Bijnsdorp et al (18) and the present study is due solely to the difference in cell lines used. In vivo, the suppression of angiogenesis may be expected as a result of COX-2 inhibition, possibly leading to the potentiation of antitumor effects.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In this study, meloxicam was not observed to have a radiosensitizing effect. it is unclear whether the discrepancy between the results of the study by Bijnsdorp et al (18) and the present study is due solely to the difference in cell lines used. In vivo, the suppression of angiogenesis may be expected as a result of COX-2 inhibition, possibly leading to the potentiation of antitumor effects.…”
Section: Discussioncontrasting
confidence: 81%
“…Several COX-2 inhibitors have been investigated for their radiosensitizing and chemosensitizing activities, as COX-2 inhibition leads to the decreased production of prostaglandins, which are involved in tumor resistance to radiation and chemotherapy (18,19,30,31). In the present study, the combined effect of meloxicam and radiation or 5-FU was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 plays important roles in tumor growth, metastasis, angiogenesis, and resistance to chemo-and radio-therapy (Shono et al, 2001;Karim et al, 2005;Bijnsdorp et al, 2007;Kang et al, 2007) and has been reported to be aberrantly overexpressed in human glioma (Joki et al, 2000;Prayson et al, 2002;Sminia et al, 2005;Buccoliero et al, 2006). Moreover, increased COX-2 expression is an independent-negative prognostic factor in malignant gliomas (Shono et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…COX-2 levels are frequently elevated in high-grade gliomas. This expression has been associated with their aggressive growth characteristics and poor prognosis for patients (34,35). Selective inhibition of COX-2 by NS-398 (a selective COX-2 inhibitor) in human gliomas in two different in vitro models reduces growth activity (36,37).…”
Section: Discussionmentioning
confidence: 99%